Critical Analysis of the Misgivings of the Book “A Critical Review of the Theoretical Fundamentals of Prophecy” on the Language of the Quran - Hamid Qorbanpour Lafmejani; Hossein Jeddi (آموزه‌های قرآنی)
In recent years, some dissident authors, including the author of A Critical Review of the Theoretical Fundamentals of Prophecy have presented critical questions and new misgivings about the topics of the language of the Holy Quran by radical and fundamental literature. This article emphasizes a critical analytical approach, in addition to repelling the misgivings of the Quranic language of the questioner and also reveals hidden layers of substantive aspects of Quranic language. These misgivings can be evaluated in three separate aspects. In the first section: To topics such as “Confusion between the lexical and cultural language of the Quran,” “the lack of boundaries between the first audience and the audiences of the later centuries” and “the time and place of revelation as a container of Divine message” and “the correspondence between the language of the messengers” and “their transnational messages” and “sending of the divine messengers to all nations” and “the coexistence of taḥaddī (Arabic: تحدّی) or the challenge of the Quran with the Arabism of the Quran and the possibility of taking advantage of its translation”. The detailed answers of the second part can also be found under the headings “the impossibility of benefiting from the translation of the Quran for everyone,” “the inadequacy of translations cannot be reconciled with the understanding of the inimitability of the Quran” (Arabic: إعجاز, ʾiʿjāz), “the time-consuming nature of teaching and learning the Arabic language of the Quran” can be found. In the final aspects, we finish the issue with answers such as “possibility of the ability of the allocation of general rules,” “proportion of miracle with advanced techniques of time,” “relativity of comparison of languages”.